The weatherman. volume 1 - Leheup, Jody (Image Comics, 2019)
Nathan Bright had it all: an awesome girlfriend, a kick-ass dog, and a job as the #1 weatherman on terraformed Mars. But when he's accused of carrying out the worst terrorist attack in human history--an event that killed nearly everyone on Earth--Nathan becomes the target of a manhunt that spans the galaxy. Can Nathan truly be responsible for such a horrific crime? And why can't he remember?--Back cover.